2011
DOI: 10.1679/aohc.73.177
|View full text |Cite
|
Sign up to set email alerts
|

<b>Expression patterns of T1R3 in duodenal epithelial cells with some gastrointestinal hormone</b>

Abstract: may regulate the secretion of serotonin by stimuli other than a mechanical one. IntroductionThe taste system, which is made up of taste receptor cells clustered in taste buds at the surface of the tongue and the soft palate, plays a key role in the decision to ingest or reject food. Its function is therefore, essential to protect organisms against harmful toxins and select the most appropriate nutrients. Ingested nutrients stimulate the secretion of gastrointestinal hormones necessary for the coordinated proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…A relationship between diabetes and the gustatory system has attracted lots of attention since the discovery of taste receptors on the intestinal epithelium where augmentation of insulin secretion is provoked through the incretin pathway. [33][34][35][36][37] Accordingly, this randomized, double-blind, placebo-controlled, cross-over study investigated the effects of long-term intake of high molecular weight fucoidan on clinical parameters, the intestinal environment, and the gustatory system controlling taste sensation in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A relationship between diabetes and the gustatory system has attracted lots of attention since the discovery of taste receptors on the intestinal epithelium where augmentation of insulin secretion is provoked through the incretin pathway. [33][34][35][36][37] Accordingly, this randomized, double-blind, placebo-controlled, cross-over study investigated the effects of long-term intake of high molecular weight fucoidan on clinical parameters, the intestinal environment, and the gustatory system controlling taste sensation in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The subgroup with an above average increase in the number of bowel movements showed a decrease of the baseline GLP-1 level, an increase of leptin and increased sensitivity to 4 tastes (except sourness) after intake of fucoidan. Recently, it was demonstrated that taste receptors are expressed throughout the entire gastrointestinal tract epithelium, [33][34][35][36][37] and that sweetness receptors in the small and large intestines are involved in the secretion of GLP-1. [44][45][46][47] In this context, it is possible that the changes of GLP-1 and the taste threshold could be due to modulation of the intestinal environment by fucoidan intake.…”
Section: Discussionmentioning
confidence: 99%